Utilization of Infocus Media in Thematic Learning Theme 5 and MIN 16 West Aceh - Ahmad Fauzi; Reti Fandayani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Media is needed in teaching so that students more easily understand the subject matter being taught. Learning media also includes a part of learning that influences teaching and learning interactions in the classroom. This study aims to determine the implementation of theme 5 infocus media on students of West Aceh MIN 16 and to determine student learning outcomes of West Aceh Min 16 theme 5 by using infocus media. This research is a class action research (CAR). Data collection was carried out directly by practicing learning using infocus media in two research cycles, namely cycle 1 and cycle 2. Based on the research results it can be concluded that the application of infocus media is proven to improve student learning outcomes in learning. This can be seen from the increase in student learning outcomes, namely in the initial conditions the percentage of student learning completeness was 39.10%, increasing to 58.33% after the implementation of cycle 1 and increasing to 79.41% after the implementation of learning cycle 2.